Identifying indicator bird species for sustainable oil palm plantation certification - Nursyamin, Zulkifli; Yahya, Muhammad Syafiq; Atikah, Sharifah Nur; Tohiran, Kamil Azmi; Norhisham, Ahmad R.; Othman, Nurul Wahida; Lechner, Alex M.; Azhar, Badrul (Elsevier, 2023)
Oil palm certification schemes such as the Roundtable on Sustainable Palm Oil (RSPO) do not consider the full suite of biodiversity indicators, such as farmland birds that are commonly found in plantations. The sole focus of certification assessments is on rare, threatened, and endangered species, yet common farmland birds, which are not conservation priority species, are an essential component of healthy agro-ecosystems. This study is the first to identify potential indicator farmland bird species for assessing oil palm environmental sustainability irrespective of farming systems or practices. Sets of candidates of oil palm bird indicator species for four sub-regions in Southeast Asia; Peninsular Malaysia, Borneo, the Philippines, and Sumatera were developed based on information gathered from previously published studies. Then, point count and opportunistic bird surveys were conducted in Peninsular Malaysia to validate our indicator bird candidates obtained from the previous step. Our results show that oil palm agro-ecosystems were dominated by common farmland birds, and rarely supported any conservation priority species. All sub-regions indicator lists comprised only Least Concern (LC) bird species except for Peninsular Malaysia where Javan Myna was recorded as Vulnerable (VU). These bird species identified provide various ecosystem services (e.g., biological pest control and pollination) and are sensitive to habitat disturbances (e.g., replanting and pesticides). Thus, they should be designated as indicator species and a key component of oil palm certification criteria. Our study also found that indicator bird species are associated with geographical locations and endemism. Therefore, we suggest using regional bird biodiversity data for developing indicator species lists to improve the environmental sustainability of oil palm cultivation for specific regions.